Minimally invasive periodontal therapy : clinical techniques and visualization technology - Harrel, Stephen K.; Wilson, Thomas G., Jr. (Ames, Iowa : Wiley Blackwell, 2014)
The long-term success of periodontal therapy is dependent on proper diagnosis and removal of subgingival tooth-borne accretions in the form of calculus and bacteria. From a clinical perspective, better visualization during the diagnostic and therapeutic phases has been shown to yield better results compared to traditional approaches. Minimally Invasive Periodontal Therapy evaluates the advantages of using minimal invasive techniques, the technologies available for enhancing visualization during minimally invasive therapy, and step-by-step illustrates the clinical use of each technique. Each chapter addresses the advantages and disadvantages of minimally invasive therapies, rationale for the approach, and the advantages and limitations of each of the current methods of improving visualization. The chapters then provide an evidence-based review of the technologies and procedures, and end with case studies for each visualization procedure, featuring clinical photographs.
Overview of minimally invasive therapy / Stephen K. Harrel and Thomas G. Wilson, Jr. -- Visualization for minimally invasive periodontal therapy : an overview / Stephen K. Harrel -- Ultrasonic endoscopic periodontal debridement / John Y. Kwan and Suzanne Newkirk -- Endoscope use in daily hygiene practice / Kara Webb and Angela Anderson -- The use of the dental endoscope and videoscope for diagnosis and treatment of peri-implant diseases / Thomas G. Wilson, Jr. -- Development of minimally invasive periodontal surgical techniques / Stephen K. Harrel -- The MIS and V-MIS surgical procedure / Stephen K. Harrel -- Minimally invasive surgical technique (MIST) and modified-MIST (M-MIST) in periodontal regeneration / Dott Pierpaolo (Sandro) Cortellini -- MI soft tissue grafting / Edward P. Allen and Lewis C. Cummings -- Future potential for minimally invasive periodontal therapy / Stephen K. Harrel and Thomas G. Wilson, Jr.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Periodontal disease -- Surgery; Dental instruments and apparatus; Dentistry -- Methods; Periodontal Diseases -- surgery; Minimally Invasive Surgical Procedures -- instrumentation; Minimally Invasive Surgical Procedures -- methods; Medical; Electronic books